Pengembangan Aplikasi Pembelajaran Bahasa Isyarat Berbasis Android Tablet - Maharoni Hendra Pradikja; Herman Tolle; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Sign language is used in the daily lives of people with hearing and speech impaired. One of the difficulties is how the deaf can inform the sign language used and can be understood by people who can hear so deaf people can communicate, interact, socialize, make friends, and dialogue occurs in everyday social. Applications